2018
DOI: 10.1021/acs.jafc.7b05261
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pickering Emulsions Stabilized by Gliadin/Proanthocyanidins Hybrid Particles (GPHPs) and the Fate of Lipid Oxidation and Digestion

Abstract: This work attempted to engineer emulsions' interface using the special affinity between proline-rich gliadin and proanthocyanidins (PA), to develop surfactant-free antioxidant Pickering emulsions with digestive-resistant properties. This binding interaction between gliadin and PA benefited the interfacial adsorption of the particles to corn oil droplets. Pickering droplets as building units assembled into an interconnected three-dimensional network structure, giving the emulsions viscoelasticity and ultrastabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(57 citation statements)
references
References 48 publications
(93 reference statements)
1
54
0
Order By: Relevance
“…However, further applications of the emulsions are limited because of poor stability and the use of surfactants. At this time, Pickering emulsions stabilized by the solid particles, with the advantages of no surfactants, high stabilities, and low cost, have garnered exponentially increasing interest in recent years [5,6]. The stability mechanism of Pickering emulsion is mainly because of the limited coalescence, bridging of droplets by a monolayer of particles, and the formation of gel network or greater steric hindrance to inhibit flocculation, coalescence or Ostwald ripening of the emulsion [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, further applications of the emulsions are limited because of poor stability and the use of surfactants. At this time, Pickering emulsions stabilized by the solid particles, with the advantages of no surfactants, high stabilities, and low cost, have garnered exponentially increasing interest in recent years [5,6]. The stability mechanism of Pickering emulsion is mainly because of the limited coalescence, bridging of droplets by a monolayer of particles, and the formation of gel network or greater steric hindrance to inhibit flocculation, coalescence or Ostwald ripening of the emulsion [7].…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic rheometer (ZX7M-AR1000, TA Instruments, New Castle, DE, USA) was used for the measurement of the rheological properties of BCNs/SPI colloidal particles and HIPEs ( 10 ). The linear viscoelastic domain of particles was determined via an oscillatory stress sweep at a fixed frequency (1 Hz) before carrying out the oscillatory measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, various food materials (such as proteins, polysaccharides, and lipids) have been widely used for the development of food-grade particles for Pickering emulsion (10)(11)(12). However, it has been demonstrated that the solid particles from proteins or polysaccharides alone display poor emulsification properties as these are used for the stabilization of HIPEs.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently claimed advantage of this type of emulsion is that no surfactants are needed, droplets are avoided, and it is very stable. For example, Zhou et al [80] showed that the combination of gliadin and proanthocyanins as the stabilizer for Pickering emulsions enhanced the antioxidant activity of the emulsion. In a study by Ju et al [81], an anthocyanin complex with black rice and soy protein isolate was used to produce Pickering emulsions.…”
Section: Emulsions and Double Emulsionsmentioning
confidence: 99%